Studi Investigasi Hubungan Antara Metakognisi, Self-regulasi dan Motivasi Belajar Siswa - Utaminingsih, Diah (Jurnal Pendidikan Progresif, 2017)
An Investigation of the relationship among metacognition, student’s self regulated learning and learning motivation. The purpose of this study is to examine the relationships among metacognition, self-regulation, and learning motivation. The sample of study consists of 130 secondary education students who were enrolled in different programs at Bandar Lampung, in Lampung. In this study, Metacognitive Learning Inventory-Science Scale adapted from An & Co (2014) was used. The relationships among metacognition (a), self-regulation (b), and learning motivation (c) were examined using correlation analysis and the hypothesis model was examined using multiple regression analysis. In correlation analysis, metacognition, and self-regulation were found positively (respectively r (a-b) = 0,430; r(a-c) = 0,584; r(b-c) = 0,497; p < 0,01). According to results metacognition was predicted positively by self-regulation and learning motivation (respectively R2 (a-b) = 18,5%; R2 (a-c) = 34,1%; R2 (b-c) = 24,1%).  Keywords:metacognition, self-regulation, learning motivationDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701